2017
DOI: 10.1111/clr.13037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implantoplasty on fracture resistance and surface roughness of standard diameter dental implants

Abstract: Objective: To assess the effect of implantoplasty on the fracture resistance, surface roughness, and macroscopic morphology of standard diameter (4.1 mm) external connection dental implants. Materials and methods:An in vitro study was conducted in 20 screw-shaped titanium dental implants with an external connection. In 10 implants, the threads and surface were removed and polished with high-speed burs (implantoplasty), while the remaining 10 implants were used as controls. The final implant dimensions were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 20 publications
3
96
2
2
Order By: Relevance
“…Implantoplasty did not affect significantly implant strength and resistance to fracture of wide diameter implants (i.e., 4.7 mm diameter; Chan et al, ). In contrast, variable results were reported for narrow/regular diameter implants (i.e., 3.75–4.1 mm diameter); in one study, a minimal reduction (i.e., 0.2 mm) in the core diameter of the implant did not significantly affect implant strength (Costa‐Berenguer et al, ), while average strength reduction of about 17%–40%—depending on implant platform/connection design—was observed in two other studies (Chan et al, ; Gehrke et al, ). In a finite element analysis (Tribst et al, ), implantoplasty resulted in a stress increase on the implant body of 44%–85%, more or less independent of the extent of simulated bone loss height, thus also of the extent—in height—of implant grinding; implantoplasty did not affect bone micro‐strain, which depended on the extent of simulated bone loss and was critical when the endo‐osseous portion of the implant was smaller than the exposed portion.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Implantoplasty did not affect significantly implant strength and resistance to fracture of wide diameter implants (i.e., 4.7 mm diameter; Chan et al, ). In contrast, variable results were reported for narrow/regular diameter implants (i.e., 3.75–4.1 mm diameter); in one study, a minimal reduction (i.e., 0.2 mm) in the core diameter of the implant did not significantly affect implant strength (Costa‐Berenguer et al, ), while average strength reduction of about 17%–40%—depending on implant platform/connection design—was observed in two other studies (Chan et al, ; Gehrke et al, ). In a finite element analysis (Tribst et al, ), implantoplasty resulted in a stress increase on the implant body of 44%–85%, more or less independent of the extent of simulated bone loss height, thus also of the extent—in height—of implant grinding; implantoplasty did not affect bone micro‐strain, which depended on the extent of simulated bone loss and was critical when the endo‐osseous portion of the implant was smaller than the exposed portion.…”
Section: Resultsmentioning
confidence: 95%
“…Kappa scores regarding agreement on the articles to be included in the full‐text analysis and those finally chosen were 0.91 and 0.95, respectively ( p < 0.001). Out of a total of 391 records assessed, 26 publications were finally included: six laboratory (Chan et al, ; Costa‐Berenguer et al, ; Gehrke, Aramburú Júnior, Dedavid, & Shibli, ; Sharon, Shapira, Wilensky, Abu‐Hatoum, & Smidt, ; de Souza Júnior et al, ; Tribst, Piva, Shibli, Borges, & Tango, ), two preclinical in vivo (Schwarz, Mihatovic, Golubovic, Becker, & Sager, ; Schwarz, Sahm, Mihatovic, Golubovic, & Becker, ), and 18 clinical publications (Englezos, Cosyn, Koole, Jacquet, & De Bruyn, ; Geremias et al, ; Matarasso et al, ; Nart, de Tapia, Pujol, Pascual, & Valles, ; Pommer et al, ; Ramanauskaite, Becker, Juodzbalys, & Schwarz, ; Romeo et al, ; Sapata, de Souza, Sukekava, Villar, & Neto, ; Schwarz et al, ; Schwarz, John, & Becker, ; Schwarz, John, Mainusch, Sahm, & Becker, ; Schwarz, John, Sahm, & Becker, ; Schwarz, John, Schmucker, Sahm, & Becker, ; Schwarz, Sahm, & Becker, ; Schwarz, Sahm, Iglhaut, et al, ; Suh, Simon, Jeon, Choi, & Kim, ; Thierbach & Eger, ). The two preclinical in vivo publications (Schwarz, Mihatovic, et al, ; Schwarz, Sahm, Mihatovic, et al, ) and the clinical of Romeo et al () and Romeo et al () publications reported on different aspects basically of the same study population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,[25][26][27] Studies have reported that the clinical prognosis of peri-implantitis resective therapy could be influenced by pre-surgical initial probing depths of more than 7mm. 20,37 Even though, various studies claim that implatoplasty may or may not induce implant fracture, 16 F I G U R E 3 Distribution of implants for follow-up time and implant failure rate implantoplasty technique could be a "promising" surgical therapy for peri-implantitis resolution. This gently reduction of the implant diameter, associated with the bone recontouring, will allow to separate the supracrestal area from the intra-bony area like in a platform switch format, counteracting possibly future MBL.…”
Section: Discussionmentioning
confidence: 99%
“…12 This approach pursuits to reduce biofilm accumulation in the rough exposed implant surfaces, since it has been reported by numerous studies that a rough surface can protect biofilm from shear forces executed by mechanical debridement, 13,14 allowing its growth and persistence as a local factor for progressive PI disease. 12,15 Nevertheless, implantoplasty has been criticized since it is a demanding technique that could increase the implant susceptibility to fracture 16,17 and the released titanium particles could induce an inflammatory process of the adjacent tissues. in vitro studies have also reported that a smooth surface enhances fibroblast adherence and consequently can help to recuperate peri-implant soft tissue health.…”
Section: Introductionmentioning
confidence: 99%